2023
DOI: 10.3390/ijms241310448
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of PRI-724 Wnt/β-Catenin Pathway Inhibitor with Vismodegib, Erlotinib, or HS-173 Synergistically Inhibit Head and Neck Squamous Cancer Cells

Robert Kleszcz,
Mikołaj Frąckowiak,
Dawid Dorna
et al.

Abstract: The Wnt/β-catenin, EGFR, and PI3K pathways frequently undergo upregulation in head and neck squamous carcinoma (HNSCC) cells. Moreover, the Wnt/β-catenin pathway together with Hedgehog (Hh) signaling regulate the activity of cancer stem cells (CSCs). The aim of this study was to investigate the effects of the combinatorial use of the Wnt/β-catenin and Hh pathway inhibitors on viability, cell cycle progression, apoptosis induction, cell migration, and expression of CSC markers in tongue (CAL 27) and hypopharynx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…For example, GANT61 combined with mTOR inhibition effectively reduces the viability of CSCs and the sphere formation of resistant cell lines in pancreatic cancer [137]. The mixture of Wnt pathway inhibitor PRI-724 and Hh pathway inhibitor vismodegib causes cell cycle arrest and downregulates the expression of OCT4 in CSCs [138]. GSK-3β and MEK inhibitors can promote tumor growth and activate the expression of downstream Wnt signaling factors, and their combined use has been shown to affect CSC maintenance and radiation sensitivity in cervical cancer [139].…”
Section: The Use Of Signal Transduction Modulators To Regulate the Tf...mentioning
confidence: 99%
“…For example, GANT61 combined with mTOR inhibition effectively reduces the viability of CSCs and the sphere formation of resistant cell lines in pancreatic cancer [137]. The mixture of Wnt pathway inhibitor PRI-724 and Hh pathway inhibitor vismodegib causes cell cycle arrest and downregulates the expression of OCT4 in CSCs [138]. GSK-3β and MEK inhibitors can promote tumor growth and activate the expression of downstream Wnt signaling factors, and their combined use has been shown to affect CSC maintenance and radiation sensitivity in cervical cancer [139].…”
Section: The Use Of Signal Transduction Modulators To Regulate the Tf...mentioning
confidence: 99%
“…Recently, interesting results were reported by Kleszcz et al, who presented a combined therapy with inhibitors of several signaling pathways in HNSCC [ 190 ]. They analyzed the therapeutic effects caused by selected inhibitors of the following signaling pathways, such as HH (vismodegib), WNT/β-catenin (PRI-724), PI3K (HS-173), and EGFR (erlotinib), separately and in combination on the tongue (CAL 27) and hypopharynx (FaDu) cancer cell lines [ 190 ]. The study showed a better response of the hypopharynx than tongue cell lines to the dual inhibition of WNT and HH signaling [ 190 ].…”
Section: Targeting the Hh Pathway In Hnsccmentioning
confidence: 99%
“…They analyzed the therapeutic effects caused by selected inhibitors of the following signaling pathways, such as HH (vismodegib), WNT/β-catenin (PRI-724), PI3K (HS-173), and EGFR (erlotinib), separately and in combination on the tongue (CAL 27) and hypopharynx (FaDu) cancer cell lines [ 190 ]. The study showed a better response of the hypopharynx than tongue cell lines to the dual inhibition of WNT and HH signaling [ 190 ]. A similar effect was observed when simultaneous inhibition with PRI-724 and erlotinib or PRI-724 and the PI3K inhibitor (HS-173) was used [ 190 ].…”
Section: Targeting the Hh Pathway In Hnsccmentioning
confidence: 99%
See 2 more Smart Citations